Towards a Restoration of the Feeling from Michel Henry´s Phenomenology of Body - Palomar Torralbo, Agustín (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The feeling takes up an important place nowadays. Our time can be termed as the aesthetic era in which the feeling has become a means of domination and control of both public and private spheres. In this social context, I have done a research into Michel Henry’s phenomenology of the body in order to rethink the feeling like a worthy source of subjective experience. Firstly, to carry out this task, I have looked into the criticism that Henry does on objectivism and idealism and, secondly, I have gone into the theory of subjectivity of the living body. This theory can be taken as the basis for an ontological foundation to think originally the feeling.